Extensive production of hydroxyl radicals during oxygenation of anoxic paddy soils: Implications to imidacloprid degradation. (January 2022) - Wang, Wenchao; Huang, Danyu; Wang, Dixiang; Tan, Mengxi; Geng, Mengyuan; Zhu, Changyin; Chen, Ning; Zhou, Dongmei
Abstract: Hydroxyl radical ( OH) plays a critical role in driving organic pollutants degradation during redox fluctuations. Such processes have been frequently investigated in sedimentary environments, but rarely referred to the agricultural fields, such as paddy soils with frequent occurrence of redox fluctuations. Our findings demonstrated that extensive OH (40.3–1061.4 μ mol kg −1 ) was produced during oxygenation of anoxic paddy slurries under circumstance conditions. Wet chemical sequential extractions, Mössbauer spectra, and X-ray photoelectron spectroscopy characterizations collectively corroborated that 0.5 M HCl-extracted Fe(II) (i.e., surface-bound Fe and Fe in low-crystalline minerals) contributed to more OH production than aqueous Fe 2+ . The produced OH can efficiently induce the oxidative transformation of organic carbon and the degradation of imidacloprid (IMP), which in turn produced the by-products, such as IMP-urea, IMP-olefin, and 6-chloronicontinic acid, via OH-attacking mechanisms. Quenching experiments showed that hydrogen peroxide (H2 O2 ) was the important intermediate for OH formation via Haber-Weiss mechanisms during oxygenation processes. These findings indicate that abundant OH can be produced during the redox fluctuations of paddy soil, which might be of great significance to predict the removal of organic contaminants and the mineralization of organic carbon in paddy fields. Graphical abstract: Image 1 Highlights: Extensive . OH production is observed in oxygenation of paddy slurries The 0.5 M HCl-extracted Fe(II) significantly contributes to . OH production OH can induce IMP degradation and oxidative transformation of organic matters. IMP-urea, IMP-olefin and 6-chloronicontinic acid are the main degradation products.